Effects of wearing of metacarpal gloves on hand dexterity, function, and perceived comfort: A pilot study. (November 2021) - Woods, SueAnn; Sosa, Eduardo M.; Kurowski-Burt, Amy; Fleming, Marissa; Matheny, Kristen; Richardson, Ashlyn; Scott, Heather; Perry, Brooke; Zornes, Isabella
Abstract: Metacarpal gloves are commonly used in heavy-duty industries such as mining and are typically thicker and bulkier than manufacturing or assembly industrial gloves. This pilot study investigates the impact of wearing metacarpal gloves on hand dexterity, functional capabilities, and perceived comfort. Four types of commercially available metacarpal gloves were selected for evaluation in a randomized controlled trial. Evaluations included turning and placing tests, also grip, pinch, and screwdriver tests, and rating of the perceived level of effort. Dexterity test results showed that metacarpal gloves significantly reduced the ability to perform motor tasks requiring coordination compared to bare hands. Hand functions such as gripping, pinching, and forearm rotations were not significantly affected. However, the perceived level of effort needed to complete those hand functions increased as the metacarpal glove's bulkiness increased. High levels of mechanical protection typically offered by metacarpal gloves can inversely affect hand dexterity and hand exertion. Highlights: Metacarpal gloves are commonly used in several heavy duty industries. Hand dexterity, function and comfort was studied. Hand dexterity is significantly affected by wearing metacarpal gloves. Hand function is not significantly affected by wearing metacarpal gloves. Perceived comfort to perform tasks reduces as the bulkiness of the glove increases.